Pengaruh Pengetahuan Investasi dan Kemajuan Teknologi terhadap Minat Gen Z dalam Berinvestasi di Pasar Modal - Damayanti, Ananda Puspa; Sulastiningsih (Jurnal Manajemen Dirgantara, 2024)
This study examines the level of investment knowledge and technological advances on Generation Z Yogyakarta's interest in investing in the capital market. Along with the times, awareness of the importance of investment is increasing, especially among the younger generation born between 1997 and 2012. Technological advances have facilitated access to information and investment transactions, which have also influenced Generation Z's interest in participating in the capital market. This study uses a quantitative approach with a sample population of 100 respondents from generation Z in Yogyakarta. Based on the results of the analysis test, it shows that the level of understanding of investment knowledge and technological advances has a significant positive influence on the variable of generation Z's interest in investing. The results of these findings are expected to provide an understanding of the factors that encourage the younger generation to invest and the importance of investment education and the use of technology in investment activities.